2008
DOI: 10.1055/s-2007-1022542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Techniques for Decompressive Lumbar Laminectomy: the Minimally Invasive versus the “Classic” Open Approach

Abstract: Bilateral decompression of lumbar spinal stenosis via a unilateral approach involves shorter operating times and less blood loss, less muscle dissection, fewer and less severe complications, and better mobility in the immediate postoperative period than open decompressive techniques. In addition, this technique is very similar to the commonly performed microendoscopic discectomy and is easily mastered over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(118 citation statements)
references
References 16 publications
4
109
2
3
Order By: Relevance
“…43 In our study, on level analysis, the mean intra-procedural EBL was 18.6 ml which is less than presented in the literature ranging between 25 and 150 ml yielded by Asgarzadie and Khoo 5 2007 and Xu et al, 56 2009 respectively. In accordance but slightly less with most of MEDL currently reported studies 7,58 the mean hospitalization days following the procedure was 1.4 days however it was more than that presented by Rahman et al, 41 2005 with mean days of 0.75. The mean operating time per level was 78.4 minutes paralleling that of Xu et al, 56 and significantly less than that yielded by Pao et al, 38 2007 and Wada et al, 52 2008.…”
mentioning
confidence: 44%
See 2 more Smart Citations
“…43 In our study, on level analysis, the mean intra-procedural EBL was 18.6 ml which is less than presented in the literature ranging between 25 and 150 ml yielded by Asgarzadie and Khoo 5 2007 and Xu et al, 56 2009 respectively. In accordance but slightly less with most of MEDL currently reported studies 7,58 the mean hospitalization days following the procedure was 1.4 days however it was more than that presented by Rahman et al, 41 2005 with mean days of 0.75. The mean operating time per level was 78.4 minutes paralleling that of Xu et al, 56 and significantly less than that yielded by Pao et al, 38 2007 and Wada et al, 52 2008.…”
mentioning
confidence: 44%
“…The mean operating time per level was 78.4 minutes paralleling that of Xu et al, 56 and significantly less than that yielded by Pao et al, 38 2007 and Wada et al, 52 2008. Dissimilar from published studies proclaimed shorter surgery time of MEDL contrasting open laminectomy, 41 Yagi et al, 58 showed 71.1 min. as a mean operative time of MEDL comparable to 63.6 min for classic laminectomy.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…It causes less traumatic injury to normal tissues surrounding the spine and is associated with less blood loss compared with open surgery. 5,8,21 Additionally, MIS techniques are associated with less postoperative pain, 9,12 better postoperative recovery, 8,9,12,21 and decreased rates of infection.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded eight comparative studies from this review because they employed a retrospective study design [7,[31][32][33][34][35][36][37]. We excluded two studies that compared techniques of posterior decompression because of concomitant fusion procedures [38,39].…”
Section: Excluded Studiesmentioning
confidence: 99%